O ENSINO DE FÍSICA NA EDUCAÇÃO DE JOVENS E ADULTOS APLICADO NA ESCOLA MUNICIPAL DE ENSINO FUNDAMENTAL MARIA DE LOURDES, BREVES-PA - SILVA, Jairo Ferreira da (2024)
This work has as main point to identify how much of previous knowledge the students of the 4th stage of the Education of Young and Adults (EYA) of the Municipal School of Elementary Education (MSEE) Maria de Lourdes, Breves-Pa, has on the subjects of Physical Sciences By means of qualitative research through a questionnaire with 6 questions. Thus, we did an analysis of the knowledge of Physics acquired by the students during the course of the studies, observing how the Physics of today is present in all places, thus portraying the importance of the content of Physics in the process of teaching and learning. Our results, obtained in two groups of 32 students from the 4 th stage of the EJA in the second semester of 2015, through the questionnaire response it was possible to observe that some questions were misinterpreted by the students, yet 81.25% acknowledged the importance of 78.5% were able to identify 5 (five) phenomena that can be explained with the aid of Physics, 87.5% could say what Physics studies demonstrating knowledge about the discipline, but 43.75% said that they will probably present difficulties in Discipline of Physics in Secondary School describing some reasons for such difficulty, among them the calculations, the class time and the fact of the teacher is not able to minister the contents of the discipline.